Visser 't Hooft, 1900-1985 Living for the Unity of the Church - Zeilstra, Jurjen (Amsterdam University Press, 2020)
God's diplomat, the pope of the ecumenical movement, but also an acerbic theologian and a difficult person: this is how journalists characterised Willem Adolf Visser 't Hooft (1900-1985). He was one of the best-known Dutch theologians outside the Netherlands and he left his mark on the world church. Even at an early age he made profound efforts in support of international ecumenical youth and student organisations (Dutch Student Christian Movement, YMCA and World Student Christian Federation). He led the World Council of Churches during its formative stages (from 1938), and after its formal establishment in 1948 became its first general secretary, serving until 1966. To Visser 't Hooft, the unity of the church was both an article of faith and of a pragmatic organisation of church influence in a disunited world.